Promotion and Price Discount Strategies in Encouraging Consumer Purchasing Decisions: A Case Study of Indomaret in Amahusu Village, Ambon - Kastanja, Jazzyca Gabriela; Janwarin, Xaverius M Y (The Journal of Financial, Accounting, and Economics, 2025)
This research is motivated by two main reasons. First, the high density of retail stores in Ambon City, including Indomaret, Alfamidi, supermarkets, and privately owned stores, has created increasingly fierce competition. To face this competition, Indomaret implements sales promotion strategies and price discounts to attract consumer interest. Second, there is a gap in previous research results regarding the effect of price discounts on purchasing decisions, so further empirical confirmation is needed. Therefore, this study aims to analyze the influence of sales promotions and price discounts on the purchasing decisions of Indomaret consumers in Amahusu Village, Ambon City. This study used a quantitative approach with a survey method and multiple regression analysis techniques. Data were collected from 207 respondents who were local Indomaret consumers. The results showed that sales promotions positively and significantly influenced purchasing decisions, as did price discounts, significantly encouraging consumer purchasing decisions. Simultaneously, both variables were also proven to influence purchasing decisions at Indomaret Amahusu positively. Thus, sales promotion and price discount strategies effectively increase consumer purchasing interest, partially and simultaneously.